Regulation of expression of the lung amiloride-sensitive Na+ channel by steroid hormones. - Champigny, G (1994)
Molecular cloning of the amiloride-sensitive Na+ channel has permitted analysis of the mechanisms of its stimulation by steroids. In rat lung cells in primary culture, where its mRNA has been detected, the activity of an amiloride-sensitive channel, highly selective for Na+, is controlled by corticosteroids. Dexamethasone (0.1 microM) or aldosterone (1 microM) induced, after a minimum 10 h treatment, a large increase of the amiloride-induced hyperpolarization and of the amiloride-sensitive current. A parallel increase in the amount of the mRNA was observed. The corresponding gene is thus a target for steroid action. Using synthetic specific agonists and antagonists for mineralo- and glucocorticoid receptors, it has been shown that the steroid action on Na+ channel expression is mediated via glucocorticoid receptors. Triiodothyronine, known to modulate steroid action in several tissues, had no effect on both the amiloride-sensitive Na+ current and the level of the mRNA for the Na+ channel protein, but potentiates the stimulatory effect of dexamethasone. The increase in Na+ channel activity observed in the lung around birth can thus be explained by a direct increase in transcription of the Na+ channel gene.